2022
DOI: 10.1007/s40123-022-00513-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Dry Eye Disease After Cataract Surgery: A Systematic Review and Meta-Analysis

Abstract: Dry eye disease (DED) after cataract surgery is associated with various risk factors, while causing a wide range of heterogeneous symptoms including decreased quality of vision. This systematic review and meta-analysis aimed to determine the prevalence and characteristics of DED after cataract surgery. We searched PubMed and EMBASE and included studies on patients with DED after cataract surgery, between January 2011 and June 2020. Study-specific estimates (DED prevalence rates after cataract surgery in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…The common risk factors for developing DED include systemic disease, systemic medications, hormone replacement therapy, and previous corneal refractive surgeries. [ 7 , 8 , 16 ] History to ascertain the presence of these should be asked. Patients complaining of dryness, grittiness, burning sensation, and itching deserve a closer look as these symptoms are suggestive of DED.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The common risk factors for developing DED include systemic disease, systemic medications, hormone replacement therapy, and previous corneal refractive surgeries. [ 7 , 8 , 16 ] History to ascertain the presence of these should be asked. Patients complaining of dryness, grittiness, burning sensation, and itching deserve a closer look as these symptoms are suggestive of DED.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…[ 5 , 6 ] Studies have shown that approximately one-tenth to one-third of patients undergoing cataract surgery have DED postoperatively. [ 7 , 8 ] Mechanisms like corneal nerve transection, inflammation, goblet cell loss, phototoxicity from the operating microscope, preservative-induced toxicity, and worsening of meibomian gland dysfunction (MGD) are the likely contributory factors. [ 9 ] Murine models of DED have shown significant increase in inflammatory infiltrates, lymphangiogenesis, and neovascularization following cataract surgery compared to non-DED models.…”
mentioning
confidence: 99%
“…Dry eye presents a wide range of subjective symptoms, including ocular dryness, eye discomfort, decreased vision, and generalized fatigue [28][29][30][31] , which demonstrates a high degree of heterogeneity in its symptomology on an individual basis. Dry eye symptoms have been reported to negatively affect one's quality of vision and work productivity, ultimately resulting in financial burden and societal economic loss [32][33][34][35][36][37][38] . However, the mainstay approach to dry eye management revolves around post-facto treatment of symptoms and suppression of further exacerbation; dry eye currently has no cure 39) .…”
Section: Symptomology Of Dry Eye and Its Stratificationmentioning
confidence: 99%
“…Additionally, DED is highly heterogeneous, with patients presenting with seemingly unpredictable combinations of the abovementioned symptoms. Therefore, patients with DED are prone to having their nonspecific presentations overlooked, and many are left undiagnosed without appropriate management [ 3 , 9 , 12 - 14 ]. There is no definitive cure for DED, and current standards of care comprise ex post facto symptom management, highlighting the importance of early diagnosis and intervention to prevent disease progression and longstanding damage [ 15 - 19 ].…”
Section: Introductionmentioning
confidence: 99%